THE STRATEGY FOR HANDLING CORRUPTION’S CRIMINAL ACTION RELATIONSHIP TO SAVING OF STATE FINANCIAL LOSSES - Bambang Tri Bawono (UNISSULA, 2020)
The massive amount of corruption that has occurred so far is closely related to the increase in state financial losses. Even though there are regulations regarding additional penalties in the form of compensation money as regulated in Article 18 of the Corruption Crime Law, the existence of this provision has not been able to return the overall state financial losses, even the total state financial losses with those saved have a significant difference. Based on this, this study examines the factors that cause state financial losses in the criminal act of corruption. Apart from that, strategies must be taken to recover from losses to state finances. The research method used in this research is library research with a normative juridical approach. The results of this study indicate that the provision of additional penalties in the form of replacement money as contained in Article 18 of the Corruption Eradication Law is basically suitable for recovering state financial losses. It's just that, the existence of such additional crimes because it is accompanied by law enforcement with a retributive justice approach which results in the crime of substitute money which cannot recover state financial losses, because the retributive justice approach requires expensive costs.